On the influence of electrode erosion on properties of nonideal plasma of underwater discharges - Starchyk, P.D.; Porytskyy, P.V. (Вопросы атомной науки и техники, 2012)
It is considered the influence of electrode erosion vapors on the transport properties of a nonideal plasma of underwater discharges at high pressure. The experimental investigation is presented on erosion evaporation and penetration into plasma. The transport coefficient set based on the Grad’s method is compared with the data obtained by using of the Lorentzian plasma theory at the same plasma composition. Also, the calculation data are considered to be in reference with transport coefficients obtained by using the Chapman-Enskog’ method. It is pointed that the nonideality effects are needed to take into consideration under calculation of properties of underwater discharge. Рассмотрено влияние материала электродов на транспортные свойства неидеальной плазмы подводных разрядов. Представлены экспериментальные результаты о проникновении продуктов эрозии электродов в плазменный канал разряда. Транспортные коэффициенты, которые рассчитывались на основе метода Грэда, сравниваются с результатами, полученными, исходя из лоренцевой теории, при одинаковом составе плазмы. Подчеркивается необходимость принятия во внимание эффектов неидеальности при расчете свойств подводных разрядов. Розглянуто вплив матеріалу електродів на транспортні властивості неідеальної плазми підводних розрядів. Представленo експериментальні результати про проникнення продуктів ерозії електродів до плазмового каналу розряду. Транспортні коефіцієнти, що були розраховані на основі методу Ґреда, порівнюються із результатами, які ґрунтувалися на лоренцевій теорії, за однаковим складом плазми. Наголошено на необхідності взяти до уваги ефекти неідеальності під час розрахунку властивостей підводних розрядів.